Ethno-cultural Processes among the Ethnic Georgians in Bursa Region (Republic of Turkey) - Gujejiani, Rozeta (Actual Problems of Kartvelology, 2025)
The article presents short history of origin of ethnic Georgians living in the republic of Turkey, Bursa Region. (Georgians living in this region were established here gradually. The fist great wave of Muhajirs in this territory took place in the 80ies of the XIX century. The second great wave dates back to 1920-1930ies). The area/map of inhabitation of Georgians and the names of compactly populated areas are specified. Besides, the main elements of traditions and culture were revealed. The attention is focused on the issues concerning the ethnic identity of Georgians, material and spiritual culture created by them (variety of their settlement, traditional houses and agricultural buildings, agricultural and other objects of everyday life, agricultural and handicraftsman implements, traditional fields of agriculture and handicraftsman, system of nutrition, spiritual and social life, forms of relationship in the family and among relatives, ways of mutual assistance in labour, ethno-musical samples and other kinds of folk materials, some innovative elements in their life, the quality of maintenance of mother tongue, problems connected with identity and maintenance of culture of ethnic Georgians, etc.) According to the ethnographic researches, alongside the settlement of ethnic Georgians, the culture of Georgian villages in Bursa region was also revealed. The settlements of ethnic Georgians exist not only in villages but also in major cities. The article also refers to the contribution of two great Georgians, inhabitants of Bursa region – Akhmed Ozkan (Melashvili) (1922-1980) and Vakhtang Malakmadze (Hairi Hairioglu) (1936-2002) who did a lot to rescue and preserve Georgian ethnic identity and culture. The article analyzes several important segments of present ethno-cultural processes: events commemorated to Akhmed Melashvili, works conducted by Ineglo Caucasus Cultural Society founded by Akhmed Melashvili, international festival ‘Chveneburebi’.